BIOM-61. FUNCTIONAL DIAGNOSTIC TESTING OF LIVE-CELL DRUG RESPONSE USING 3D PATIENT DERIVED GLIOBLASTOMA SPHEROIDS ON THE INCUCYTE PLATFORM. (9th November 2020) - Malinowski, Seth; Touat, Mehdi; Stockslager, Max; Giglio, Ross; Geduldig, Jack; Sinai, Claire; Pelton, Kristine; Reardon, David; Wen, Patrick; Chow, Kin Hoe; Manalis, Scott; Ligon, Keith
Abstract: Three-dimensional patient derived cultures hold great potential for use as personalized functional diagnostics, enabling more accurate preclinical evaluations of drug treatments compared to conventional cell lines. Optical imaging of live cells allows for continuous, time lapsed measurements, and can provide drug response data based on rich phenotypic changes of cell cultures. However, current imaging techniques based on 2D microscopy evaluation aren't readily adaptable to evaluate the drug response of intact spheroids, which may better represent the in vivo environment and retain critical cellular interactions within the tumor microenvironment. Using the IncuCyte live cell imaging platform, we successfully imaged a large cohort (n = 77) of patient derived glioblastoma spheroid cultures and evaluated whether changes in sphere volume could be used as a direct measure of treatment response. Improving on the default Incucyte analysis software, we developed an R data processing pipeline better suited for spheroid measurements, which quantified the heterogeneity in GBM baseline spheroid growth, and calculated a drug response score based on spheroid changes in response to DNA damaging agents (TMZ as an example). Compared to conventional viability measurements, this novel 3D drug response score was found to accurately identify both drug sensitive and resistant spheroids and showed robust concordance with genomic biomarkers of response (NGS and MGMT promoter methylation) and patient outcomes. Additionally, we coupled the 3D drug score with known genetic data to explore other key pathways and genes involved in TMZ response. We provide here novel analysis methods and public code (Github) to advance the use of IncuCyte spheroid measurements, and deconvolute 3D spheroid drug response into a quantifiable statistic. These methods are adaptable to freshly isolated patient cells for rapid evaluation of treatment response in GBM patients while remaining widely applicable to other cancers such as pancreatic, colon, and non-cancer organoids/spheroids with 3D growth.